2018
DOI: 10.15430/jcp.2018.23.4.170
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-growth Effects of Imatinib and GNF5 via Regulation of Skp2 in Human Hepatocellular Carcinoma Cells

Abstract: BackgroundHuman hepatocellular carcinoma (HCC) is a common liver tumor and the main cause of cancer-related death. Tyrosine kinase inhibitors, such as imatinib and GNF5 which were developed to treat chronic myelogenous leukemia, regulate the progression of various cancers. The aim of this study was to confirm the anti-tumor activity of tyrosine kinase inhibitors through regulation of S-phase kinase-associated protein 2 (Skp2), an important oncogenic factor in various cancer cells, in human hepatocarcinoma SK-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It was found using caspase-3 activity assays that the cell death elicited by the TKIs was mediated by apoptosis in all cases, which has been observed by other researchers in CML and other cancer cell lines [53][54][55][56]. Apoptosis can be induced by many cellular processes; however, one of the most common initiators of this process is oxidative stress [57][58][59].…”
Section: Discussionsupporting
confidence: 52%
“…It was found using caspase-3 activity assays that the cell death elicited by the TKIs was mediated by apoptosis in all cases, which has been observed by other researchers in CML and other cancer cell lines [53][54][55][56]. Apoptosis can be induced by many cellular processes; however, one of the most common initiators of this process is oxidative stress [57][58][59].…”
Section: Discussionsupporting
confidence: 52%
“…Imatinib has been reported to exhibit potent therapeutic effects in various cancers [ 20 - 22 ]. Our previous study has revealed that imatinib and GNF-5 induce HCC cells apoptosis by inhibiting the expression of Skp2 and p-AKT [ 15 ]. In the present study, we evaluated the effect of imatinib and GNF-5 on HCC cell growth and cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib (Gleevec, Glivec) is a synthetic tyrosine kinase inhibitor of the breakpoint cluster region-Abelson murine leukemia (Bcr-Abl) fusion gene and is used in the treatment of chronic myeloid leukemia (CML) [ 12 ]. Imatinib has also been used to treat gastrointestinal stromal tumors and various other malignancies [ 13 - 15 ]. GNF-5 is a selective, non-ATP-competitive inhibitor of Bcr-Abl and is used in combination with an ATP-competitive inhibitor, such as imatinib or nilotinib, to enhance antitumor effects in vitro [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinically, GNF-2, GNF-5, and ABL-001 have all been effective against solid tumors and/or on tumor cell lines expressing high levels of ABL1/ABL2 (30)(31)(32)(33). In 2009, GNF-2 was shown to inhibit the enzymatic and cellular kinase activities of ABL1, ABL2, and recombinant ABL and to inhibit the proliferation of BCR-ABL1-expressing Ba/F3 fibroblast cells at a potency comparable to that of imatinib (IC 50 ¼ 0.24 mmol/L; ref.…”
Section: Hematologic and Solid Malignanciesmentioning
confidence: 99%
“…In 2018, Kim and colleagues found that the more pharmacokinetically active derivative of GNF-2, GNF-5, can inhibit the growth of human hepatocellular carcinoma (SK-HEP1) cells-increasing the expression of tumor suppressors (p27 and p21) alongside markers of apoptosis such as caspases and PARP (33). Further, Malki and colleagues designed several alloxazine derivatives of imatinib that also bind to ABL kinases' allosteric sites (34).…”
Section: Hematologic and Solid Malignanciesmentioning
confidence: 99%